Detailed Study of Stars and Gas in a z = 8.3 Massive Merger with Extreme Dust Conditions - Anishya Harshan; Roberta Tripodi; Nicholas S. Martis; Gregor Rihtaršič; Maruša Bradač; Yoshihisa Asada; Gabe Brammer; Guillaume Desprez; Vince Estrada-Carpenter; Jasleen Matharu; Vladan Markov; Adam Muzzin; et al. (The Astrophysical Journal Letters)
We present galaxy MACS0416-Y1 at z _spec = 8.312 as observed by the CAnadian NIRISS Unbiased Cluster Survey. MACS0416-Y1 has been shown to have extreme dust properties; thus, we study the physical properties and star formation histories of its resolved components. Overall, we find that MACS0416-Y1 is undergoing a star formation burst in three resolved clumps. The central clump is less massive compared to the other clumps and possibly formed in the merging process of the two larger clumps. Although the star formation history indicates an ongoing star formation burst, this gas-rich galaxy shows comparable star formation efficiency to cosmic noon galaxies. Using NIRSpec prism spectroscopy, we measure metallicity, $12+log{\rm{(O/H)}}=7.76± 0.03$ , ionization parameter, $logU=-2.48± 0.03$ , and electron temperature T _e = 18000 ± 4000 K. The emission line ratios of the galaxy indicate an evolved interstellar medium similar to z ∼ 2 star-forming galaxies. Further, we find possible presence of ionization from an active galactic nucleus (AGN) using emission line diagnostics; however, we do not detect a broad-line component in the H β emission line. As this gas-rich galaxy is undergoing a major merger, we hypothesize that the high dust temperature in MACS0416-Y1 is caused by the star formation burst or a possible narrow-line AGN.